2020
DOI: 10.1007/s12011-020-02433-z
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Iron and Zinc Supplementation on Iron Apparent Absorption in Rats Fed Vitamins and Minerals Reduced Diets

Abstract: Deficient human diet is usually reduced in many nutrients, but animal studies on iron absorption have been only carried out for rats fed well-balanced (control) and iron-deficient diets. The aim of this study was to evaluate the effect of iron or iron/zinc supplementation on iron apparent absorption (IAA) in rats fed a diet reduced in all vitamins and minerals (R). The study was conducted on 77, 6-week-old male Wistar rats in 3 stages as follows: stage I, 4-week period of adaptation to R diet (50% less vitamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…AA of micronutrients describe their bioavailability in diet (Kondaiah et al, 2019). In this experiment, we found that both agronomic and genetic Zn biofortification significantly ( p < .05) decrease FeAA which may be related with higher Zn saturation in intestine, because both Fe and Zn use same channels for absorption in body (Kondaiah et al, 2019; Rolf et al, 2021). Lower decrease in Zincol‐2016 FeAA seems to be associated with its significantly ( p = .0001) reduced phytate content as compared to Johar‐2016, that inhibits Fe absorption in the body (Kondaiah et al, 2019).…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…AA of micronutrients describe their bioavailability in diet (Kondaiah et al, 2019). In this experiment, we found that both agronomic and genetic Zn biofortification significantly ( p < .05) decrease FeAA which may be related with higher Zn saturation in intestine, because both Fe and Zn use same channels for absorption in body (Kondaiah et al, 2019; Rolf et al, 2021). Lower decrease in Zincol‐2016 FeAA seems to be associated with its significantly ( p = .0001) reduced phytate content as compared to Johar‐2016, that inhibits Fe absorption in the body (Kondaiah et al, 2019).…”
Section: Discussionmentioning
confidence: 69%
“…Therefore, higher dietary Zn intake did not warrant better Zn nutrition, but it should be studied along with its absorbable amount (termed as retained here). Significant (p < .05) decrease in ZnAA with genetic and agronomic biofortification (Figure 1) may relate to higher Zn saturation in the animals intestine (Kondaiah et al, 2019;Rolf et al, 2021), as Zn excretion increased (Supporting Information: Table S2 and Table 5). Similar results have been depicted in Quails fed on Zn biofortified wheat: an increase in Zn intake and excretion (Sahin et al, 2021).…”
Section: Zn Biofortification Improves Zn In Blood and Tissuesmentioning
confidence: 99%
“…Zinc and iron can bind due to the chemical similarities between the two trace elements. Therefore, the inhibitory effect of zinc on iron absorption (and vice versa) may be related to zinc antagonistic to iron absorption in the intestinal tract (Rolf et al, 2021). The absorption and transport mechanisms of zinc and iron are chemically similar.…”
Section: Resultsmentioning
confidence: 99%
“…Zinc is one of the essential trace element that is necessary for the development and growth at all stages of organisms and plays an important role as coenzyme in many reactions (Rolf et al 2021). A long-term elevation of IL-6 is thought to be responsible for severe lung damage to the immune system and macrophage excitation syndrome.…”
Section: Resultsmentioning
confidence: 99%
“…Scientific evidence supports that pumpkin possesses various biological properties, such as antifatigue, antioxidant, and anti-inflammatory effects (11,39). The health benefits of pumpkin seeds may be attributed to their composition of several macro-and micronutrients, including proteins, triterpenes, lignans, phytosterols, polyunsaturated fatty acids, antioxidative phenolic compounds, carotenoids, tocopherol, and minerals (11,39,40). The recommended dietary allowances (RDAs) for trace elements, including Zn, Mg, iron, manganese, and Cu, are as follows: 15 mg/day for Zn, 420 mg/day for Mg, 18 mg/day for Iron, 2.3 mg/day for manganese, and 3 mg/day for Cu, for adults (5,41).…”
Section: Pumpkin Seed Oil Supplementation On the Serum Liver And Gast...mentioning
confidence: 95%